2018
DOI: 10.1016/j.celrep.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Growth Is Regulated via Acquired Leptin Resistance and Engages a Pomc-Somatostatin-Growth Hormone Circuit

Abstract: SUMMARY Anorexigenic pro-opiomelanocortin (Pomc)/alpha-melanocyte stimulating hormone (αMSH) neurons of the hypothalamic melanocortin system function as key regulators of energy homeostasis, also controlling somatic growth across different species. However, the mechanisms of melanocortin-dependent growth control still remain ill-defined. Here, we reveal a thus-far-unrecognized structural and functional connection between Pomc neurons and the somatotropic hypothalamo-pituitary axis. Excessive feeding of larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…More recently, Riddle and colleagues reported that cavefish, Mexican tetra ( Astyanax mexicanus ) which carries a mutation in the insulin receptor lead to insulin resistance, and this phenotype is beneficial to weight gain for survival in nutrient-limited environment ( 44 ). Moreover, the occurrence of LR in zebrafish larvae promoted excessive caloric intake when food resources were plentiful, suggesting LR could be an ancient mechanism to promote somatic growth ( 45 ). In the present two different DIO Nile tilapia models, carbohydrate represents the main energy source in HCD while lipid is the main one in HFD.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Riddle and colleagues reported that cavefish, Mexican tetra ( Astyanax mexicanus ) which carries a mutation in the insulin receptor lead to insulin resistance, and this phenotype is beneficial to weight gain for survival in nutrient-limited environment ( 44 ). Moreover, the occurrence of LR in zebrafish larvae promoted excessive caloric intake when food resources were plentiful, suggesting LR could be an ancient mechanism to promote somatic growth ( 45 ). In the present two different DIO Nile tilapia models, carbohydrate represents the main energy source in HCD while lipid is the main one in HFD.…”
Section: Discussionmentioning
confidence: 99%
“…R26-fl-rxΔ-ZsGreen mice have been previously described ( Löhr et al., 2018 ). Homozygous mice were mated with MCH-Cre tg/wt mice to generate ZsGreen MCH mice.…”
Section: Methodsmentioning
confidence: 99%
“…Overfeeding per se led to glucose intolerance in fish independent of genotype, and loss of leptin function in addition to overfeeding did not impair glucose tolerance further. One recent study found that overfeeding of zebrafish larvae leads to leptin resistance and reduced hypothalamic pomca levels, leading to activation of the melanocortin system, elevation of growth hormone levels, and enhanced somatic growth [48]. Together, these data point towards a fundamentally differential physiological role for leptin depending on nutrient availability.…”
Section: Discussionmentioning
confidence: 99%